DETERMINANT FACTORS INFLUENCING HOUSEWIVES TO USE PEER-TO-PEER LENDING SERVICES TO SUPPORT FAMILY FINANCES - Wahidiyah, Rahmatul 'Aini; Putra, Yuniarti Hidayah Suyoso; Yudhiyati, Ratna (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This study aims to examine the influence peer to peer-to-peer lending services on housewives in Malang City in supporting family finance. Perceived ease of use, perceived usefulness, perceived risk, and financial literacy are predicted as determinant factors that can attract interest and the use peer to peer-to-peer lending services by housewives to cover family finances. This research uses a quantitative descriptive approach with Partial Least Square for the analysis method. The questionnaire was developed using extended Technology Acceptance Model theoretical framework and distributed directly to 121 housewives in Malang City. The findings show that perceived ease of use has a negative effect on intention to use, while perceived usefulness, perceived risk, and financial literacy have a positive effect on intention to use. Furthermore, perceived risks, financial literacy, and perceived ease of use have negative effects on the Actual system use, meeanwhile intention to use and perceived usefulness have a positive effect on actual system use